Long-Term Results of Excimer Laser Surface Ablation with Smoothing for High Myopia - Vinciguerra, Paolo; Torres, Ingrid; Sergio, Adriana; Legrottaglie, Emanuela F.; Camesasca, Fabrizio I. (Journal of Ocular Diseases and Therapeutics, 2017)
Purpose: To evaluate long-term refractive, aberrometric and anatomical results of surface ablation plus corneal PTK-style smoothing for myopia greater than –7.00 D. Methods: One-hundred-and-fourteen eyes of 69 patients (mean age: 37.7 ± 8.3 years) underwent PRK with the NIDEK EC-5000 excimer laser (NIDEK Co. Ltd., Gamagori, Japan) using multiple optical zones ranging in diameter from 4.89 mm to 7.0 mm, and transition zones (TZ) that were at least 3 mm wider than the optical zones (OZ). A cross-cylinder technique was used for treating astigmatism greater than 0.50 D. All eyes underwent a phototherapeutic keratectomy (PTK) smoothing technique using masking fluid. The Student’s t-test was used to determine a statistically significant change after surgery. A p value less than 0.05 was considered statistically significant. Results: Preoperative corrected distance visual acuity (CDVA) was 0.88 ± 0.16 with –9.53 ± 1.18 D cycloplegic spherical equivalent (SE). Preoperative corneal pachymetry was 560.4 ± 30.1 µ. Three years after surgery uncorrected visual acuity (UCVA) was 0.79 ± 0.26, CDVA was 0.92 ± 0.19 with –0.56 ± 0.90 D SE. Mean corneal haze was highest 1 month after surgery (0.58 ± 0.35), then progressively decreased to 0.11 ± 0.32 by 3 months postoperatively. Following year one, refraction and corneal curvature remained stable. There were no cases of keractasia to date. There was no hyperopic induction due to PTK. Two eyes required retreatment due to undercorrection. Total wavefront error did not change significantly, while astigmatism decreased and coma increased (both with p< 0.001). Conclusion: Surface ablation for the treatment of high myopia using PTK smoothing with a masking fluid was safe and effective. Wide optical and transition zones prevented induction of spherical aberration and the incorporation of the smoothing technique created a regular corneal surface with regular healing and trace to no haze after surgery.